Analysis of Strategies to Improve Service Provider Hand Hygiene Compliance at Dono Tulungagung Community Health Center - Byba Melda Suhita; Danang Andhika; Amrul Chasanah; Meidya Sri Wulandari; Nanik Azizah (Journal of Community Engagement in Health, 2024)
The problem found at the Dono Tulungagung Community Health Center was a decrease in the hand hygiene compliance achievements of health service providers who did not meet the National Health Center Quality Indicator target of 85%. The aim of this research is to analyze strategies for increasing hand hygiene compliance achievements. This research uses a qualitative method with a descriptive analysis approach. Primary data was obtained through direct interviews with sources. The analysis uses fishbone diagrams to identify problems, the USG (Urgency, Seriousness, Growth) method to determine problem priorities and SWOT analysis (Strength, Weakness, Opportunity, Threat) to identify strategies in determining intervention plans. Based on the results of the fishbone, USG and SWOT analysis, the implementation strategy that can be implemented is to re-socialize hand hygiene material and the importance of maintaining hand hygiene compliance for all service providers at the Dono Tulungagung Community Health Center and updating posters on each sink wall as a reminder and instructions on how to wash hands correct.